Kinins and Their Receptors in Infectious Diseases - Ana Paula A. Dagnino; Maria M. Campos; Rodrigo B. M. Silva (MDPI AG, 2020)
Kinins and their receptors have been implicated in a series of pathological alterations, representing attractive pharmacological targets for several diseases. The present review article aims to discuss the role of the kinin system in infectious diseases. Literature data provides compelling evidence about the participation of kinins in infections caused by diverse agents, including viral, bacterial, fungal, protozoan, and helminth-related ills. It is tempting to propose that modulation of kinin actions and production might be an adjuvant strategy for management of infection-related complications.